2022
DOI: 10.3390/ma15113992
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Interactions and Order–Disorder Transition in FCC-Type FeCoNiAl1−xTix High-Entropy Alloys

Abstract: Single-phase high-entropy alloys with compositionally disordered elemental arrangements have excellent strength, but show a serious embrittlement effect with increasing strength. Precipitation-hardened high-entropy alloys, such as those strengthened by L12-type ordered intermetallics, possess a superior synergy of strength and ductility. In this work, we employ first-principles calculations and thermodynamic simulations to explore the atomic interactions and order–disorder transitions in FeCoNiAl1−xTix high-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Zhao et al [15,16] studied the microstructure evolution, hardness and wear resistance of HEMB-Ni 2 B composite coating via first principle methods; the results show that the synergistic effect between the superhardness of HEMB and the large plastic deformation ability of Ni 2 B can significantly improve the wear resistance of HEMB-Ni 2 B coatings, with a friction coefficient as low as 0.13. Similar investigations have been also reported in references [15][16][17][18][19][20][21][22][23]. Yu et al [17] demonstrated that the structure of Al x CoCrFeNi HEA transforms from a single FCC phase to an FCC + BCC dual phase with the increases in Al contents.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Zhao et al [15,16] studied the microstructure evolution, hardness and wear resistance of HEMB-Ni 2 B composite coating via first principle methods; the results show that the synergistic effect between the superhardness of HEMB and the large plastic deformation ability of Ni 2 B can significantly improve the wear resistance of HEMB-Ni 2 B coatings, with a friction coefficient as low as 0.13. Similar investigations have been also reported in references [15][16][17][18][19][20][21][22][23]. Yu et al [17] demonstrated that the structure of Al x CoCrFeNi HEA transforms from a single FCC phase to an FCC + BCC dual phase with the increases in Al contents.…”
Section: Introductionsupporting
confidence: 84%
“…Zhang et al [19] found that the surface roughness is the smallest of CoCrFeNiAl X (x = 0, 0.6, 1) with a 0.6 wt% Al addition. Wu et al [20] reported that the transition temperature from order to disorder in FeCoNiAl 1−x Ti x decreases with the increase in Ti content. Zhang et al [22] showed that the average microhardness of the AlCoCrFeNiTi 0.5 HEA coating reached 989 HV, which was 32% higher than AlCoCrFeNi and reduced wear by 85%.…”
Section: Introductionmentioning
confidence: 99%